Ecohydrology : Darwinian expression of vegetation form and function - Eagleson, Peter S. (Cambridge University Press, 2002)
"Ecohydrology bridges the fields of hydrology and ecology and proposes new unifying principles derived from the concept of natural selection. It also has potential application in determining the response of vegetation to slow variations in climate. This book will therefore provide fascinating reading for graduate-level students and research scientists working in the fields of ecohydrology, hydroclimatology, forest ecology, and surface water hydrology."--Jacket